Prioritised challenges and critical success factors for delivering quality education in Malaysian private higher education institutions - Anis, Azilah; Islam, Rafikul (Emerald Publishing House, 2019)
Purpose - The paper develops a hierarchical model to rank the challenges faced by the private Malaysian Higher Education Institutions (HEIs) in the provision of quality education and subsequently their corresponding critical success factors (CSFs) to address those challenges.